2004
DOI: 10.1111/j.1365-2672.2004.02202.x
|View full text |Cite
|
Sign up to set email alerts
|

Monoacylglycerols: glycolipid biosurfactants produced by a thermotolerant yeast, Candida ishiwadae

Abstract: Aims: To isolate and characterize biosurfactants produced by a thermotolerant yeast isolated in Thailand. Materials and Results: Yeast strains isolated from plant material in Thailand were first screened for the ability to produce lipase and biosurfactant. A strain Y12, identified as Candida ishiwadae by physiological tests, survived at 45°C and produced relatively large amounts of biosurfactants. From the culture filtrate of this strain, two glycolipid biosurfactants, a and b, were purified by solvent fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 8 publications
0
28
0
4
Order By: Relevance
“…Haba et al 36 compared the composition of used olive and sunflower oils with the standard unused oils in their study and found that the most important difference is the presence of 22.52 wt% of fatty acids of low chain length (<C 14 ) in used oil. Thanomsub et al 37 isolated yeast strains from plant material in Thailand and a strain of Candida ishiwadae was able to produce glycolipid biosurfactants from used soybean cooking oil. The biosurfactants produced were characterized to be monoacylglycerols and exhibited high surfactant activities.…”
Section: Carbon Source From Renewable Resourcesmentioning
confidence: 99%
“…Haba et al 36 compared the composition of used olive and sunflower oils with the standard unused oils in their study and found that the most important difference is the presence of 22.52 wt% of fatty acids of low chain length (<C 14 ) in used oil. Thanomsub et al 37 isolated yeast strains from plant material in Thailand and a strain of Candida ishiwadae was able to produce glycolipid biosurfactants from used soybean cooking oil. The biosurfactants produced were characterized to be monoacylglycerols and exhibited high surfactant activities.…”
Section: Carbon Source From Renewable Resourcesmentioning
confidence: 99%
“…Com o acúmulo desses resíduos, tem aumentado o interesse na utilização desses materiais como fonte de nutrientes para transformação microbiana. 46 Thanomsub et al 47 utilizaram como fonte de carbono o óleo de soja queimado, proveniente da fritura, para produção de um biossurfactante glicolipídico a partir de Candida ishwadae. Este surfactante exibiu alta atividade de emulsificação.…”
Section: Fontes De Carbono De Origens Renováveisunclassified
“…Diferentes compostos nitrogenados têm sido empregados na produção de biossurfactantes, tais como licor de milho, milhocina, 58 uréia, 21 peptona, 13 extrato de levedura, 8,9,23,59 sulfato de amônio, 19 nitrato de amônio, 47 nitrato de sódio, 48 dentre outros como extrato de carne, farelo de soja e extrato de malte. 60 O extrato de levedura é a fonte de nitrogênio mais utilizada para a produção de biossurfactantes, mas sua concentração varia de acordo com o microorganismo e o meio de produção.…”
Section: Fonte De Nitrogêniounclassified
“…Growth properties at high temperatures vary from strain to strain, suggesting that tolerance to high temperature stems from a complex genetic background. Although thermotolerant yeasts have been isolated from tropical habitats (e. g., Thanomsub et al, 2004), mutational improvement of labEdited by Hideo Shinagawa * Corresponding author. E-mail: shimoda@sci.osaka-cu.ac.jp oratory strains has scarcely been successful.…”
Section: Introductionmentioning
confidence: 99%